equaçoes
x-(2x-1)=23
2x-(x-1)=5-(x-3)
Soluções para a tarefa
Respondido por
10
x-(2x-1)=23
x-2x+1=23
x-2x=23-1
-x= 22
x= 22
2x-(x-1)=5-(x-3)
2x-x+1=5-x+3
2x-x+x=5+3-1
2x=7
x=7/2
x-2x+1=23
x-2x=23-1
-x= 22
x= 22
2x-(x-1)=5-(x-3)
2x-x+1=5-x+3
2x-x+x=5+3-1
2x=7
x=7/2
Respondido por
1
x-(2x-1)=23 (distributiva do sinal negativo)
x-2x+1=23
x+1=23
x=23-1
x=22
2x-(x-1)=5-(x-3) (faz a distributiva do sinal)
2x-x+1=5-x+3
x+1=5-x+3
x+x+1=5+3
2x+1=8
2x=8-1
2x=7
x=7/2
qualquer duvida, pergunte ;)
x-2x+1=23
x+1=23
x=23-1
x=22
2x-(x-1)=5-(x-3) (faz a distributiva do sinal)
2x-x+1=5-x+3
x+1=5-x+3
x+x+1=5+3
2x+1=8
2x=8-1
2x=7
x=7/2
qualquer duvida, pergunte ;)
Perguntas interessantes
História,
1 ano atrás
Artes,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás